TRANSFORMASI SIKAP MESIR TERHADAP HAK ASASI PEREMPUAN: SEBUAH PERBANDINGAN DENGAN NOVEL IMRA’AH NUQTHAH AL-SHIFR - Rosalinda; Nurdin; Dian Mursyidah (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
Middle Eastern countries, including Egypt, are among those identified through various surveys as having high levels of discrimination against women's human rights. One of the main contributing factors is the dominant patriarchal system prevailing in Arab nations. However, over time, a transformation in societal attitudes has occurred. This article aims to examine the transformation of Egypt’s stance on human rights, particularly women’s rights, by using the realist novel Imra`ah ‘Inda Nuqṭah Al-Ṣifr, written in 1973 by Egyptian feminist Nawal El Saadawi, as a comparative lens. The novel is considered a realist portrayal of women’s conditions in Egypt at the time. This article is grounded in human rights theories from both Western and Islamic perspectives, as well as feminist theories from prominent feminist figures. Using a qualitative descriptive research method, the study finds that at the time Imra`ah ‘Inda Nuqṭah Al-Ṣifr was written, women in Egypt faced significant discrimination, including political inequality, educational subordination, and limited family rights. However, a shift occurred during Anwar Sadat’s presidency in 1981, when Egypt became one of the Muslim-majority countries that supported international human rights documents, particularly in efforts to eliminate gender-based discrimination. Egypt ratified the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), albeit with reservations on articles related to Islamic Sharia as the foundation of family law in Egypt. Under the current leadership of President Abdel Fattah el-Sisi, Egyptian women have gained broader access to education and other rights. Today, it is not uncommon to see Egyptian women driving, going out unaccompanied by their husbands, and spending evenings at cafés smoking shisha. Women have also gained greater political access, with some occupying key positions, such as the Governor of Alexandria. Nonetheless, certain roles, such as the position of ifta’ (Islamic legal opinion), remain largely male-dominated.